OP14 Progress In Use Of Telerehabilitation For Persons With COPD. (2019) - Hailey, David; Roine, Risto
Abstract : Introduction: Telerehabilitation shows promise in many fields though strong evidence of benefit has been limited. We reviewed progress in the use of telerehabilitation for persons with chronic obstructive pulmonary disease (COPD). A challenge in caring for persons with this condition is the ability to achieve high levels of patient participation and compliance with rehabilitation processes. Methods: Relevant publications were identified through literature searches from November 2009 to May 2018. We selected those that described studies of telerehabilitation in the management of COPD and reported clinical or administrative outcomes. Study quality was assessed using an approach that considers both study performance and study design. Judgments were made on whether the telerehabilitation application had been successful, if reported outcomes were clinically significant, and if further data were needed to establish the application as suitable for routine use. Results: Twenty-five publications, on 26 studies, were selected. Twelve were of high or good quality. In 11 studies the telemedicine application was successful. Nine studies had unsuccessful applications, and for six studies success was unclear. Further data before routine use would be required or desirable for all successful applications. In many studies there were difficulties associated with availability of skilled mentors, motivational support for patients and access to reliable remote monitoring and communication technology. Conclusions: Various types of telerehabilitation are potentially helpful in the management of COPD. Availability and access to these technologies should improve. However, in management of this clinically challenging condition their use must be linked to suitable training and education of patients with COPD and timely support for them from healthcare professionals.